Defective antifungal immunity in patients with COVID-19 - Morton, Charles Oliver; Griffiths, James S.; Loeffler, Juergen; Orr, Selinda; White, P. Lewis (Frontiers in Immunology, 2022)
The COVID-19 pandemic has placed a huge strain on global healthcare and been a significant cause of increased morbidity and mortality, particularly in at-risk populations. This disease attacks the respiratory systems and causes significant immune dysregulation in affected patients creating a perfect opportunity for the development of invasive fungal disease (IFD). COVID-19 infection can instill a significant, poorly regulated pro-inflammatory response. Clinically induced immunosuppression or pro-inflammatory damage to mucosa facilitate the development of IFD and Aspergillus, Mucorales, and Candida infections have been regularly reported throughout the COVID-19 pandemic. Corticosteroids and immune modulators are used in the treatment of COVID-19. Corticosteroid use is also a risk factor for IFD, but not the only reason for IFD in COVID -19 patients. Specific dysregulation of the immune system through functional exhaustion of Natural killer (NK) cells and T cells has been observed in COVID-19 through the expression of the exhaustion markers NK-G2A and PD-1. Reduced fungicidal activity of neutrophils from COVID-19 patients indicates that immune dysfunction/imbalance are important risk factors for IFD. The COVID-19 pandemic has significantly increased the at-risk population for IFD. Even if the incidence of IFD is relatively low, the size of this new at-risk population will result in a substantial increase in the overall, annual number of IFD cases. It is important to understand how and why certain patients with COVID-19 developed increased susceptibility to IFD, as this will improve our understanding of risk of IFD in the face of future pandemics but also in a clinical era of increased clinical immuno-suppression/modulation.